Estetika Ragam Gerak dalam Tarian Kinyah Mandau Suku Dayak Ngaju Kalimantan Tengah - Ripaldo, Ripaldo; Defa, Dyas (Gesture: Jurnal Seni Tari, 2025)
The purpose of this study is so that readers can find out the aesthetics of the variety of movements in the Kinyah Mandau Dance of Central Kalimantan. The Kinyah Mandau Dance is a war dance originating from the Dayak Ngaju Tribe of Central Kalimantan. This dance depicts the unity and togetherness of the Dayak people in maintaining defense and security. In this study used a qualitative research method using a case study approach and literature study. The aesthetic values ​​contained in the Kinyah Mandau dance movements refer to elements of beauty, courage, technique and agility of movement, visual side, philosophical value, and cultural expression. From the results of the study, there are several varieties of movements in the Kinyah Mandau Dance, namely the Tasai Manasai, Manangking Mandau, Mahunus Mandau and Menggigit Mandau movements. The Tasai Manasai movement is a graceful hand movement and footsteps that follow the rhythm of the music, the Manangking Mandau movement reflects the dancer's skill and dexterity in playing the Mandau weapon. The Mahunus Mandau movement requires precision in drawing (lifting) the weapon with the right technique and good coordination with the hands and body, and the Menggigit Mandau movement describes the agility of beauty in dancing by biting the Mandau.